A Novel Model for Building Digital Infrastructure for Biodiversity Studies. (January 2021) - Dhindsa, A; Bhatia, S; Agrawal, S; Sohi, B S
Abstract: In this research work, a novel proposal has been given to build a digital infrastructure for conducting Biodiversity studies. The proposed system allows citizens and professionals to come together and work on a common platform. This system supports different types of data such as protein, gene, video, image, text, and sound which enables it to support all kinds of instrumentation. Also, this system can be used for connecting telescopes, probes, sensors, cameras, and microscopes with the cloud and data can be stored in real time. The system allows the use of international standards such as Global Biodiversity Information Facility (GBIF) for building biodiversity data. It is a collaborative system where discussion on identification and validation of the organisms can be done through seamless integration with third party applications.